Dealing with ignored attributes in choice experiments on valuation of Sweden's environmental quality objectives - Fredrik Carlsson; Mitesh Kataria; Elina Lampi (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Using a choice experiment, this paper investigates how Swedish citizens value three environmental quality objectives. In addition, a follow-up question is used to investigate whether respondents ignored any attributes when responding. The resulting information is used in the model estimation by restricting the individual parameters for the ignored attributes to zero. When taking the shares of respondents who considered both the environmental and the cost attributes (52-69 percent of the respondents) into account, then the WTPs for each attribute change if the respondents who ignored the attributes have a zero WTP. At the same time, we find evidence that not all respondents who claimed to have ignored an attribute really did. However, the most commonly ignored non-monetary attributes always have the lowest rankings in terms of WTP across all three environmental objectives. Thus, our results show that instead of ignoring, respondents seem to put less weight on the attributes they claimed to have ignored.
Keywords: D61; Q50; Q51; 330; Choice experiment; environmental quality objectives; follow-up question; ignoring attributes; WTP; Umweltschutz; Umweltpolitik; Umweltqualität; Public Choice; Test; Willingness to pay; Schweden